Psychoactive pharmaceutical residues in the watersheds of Galicia (Spain) Fármacos psicoactivos en las cuencas de Galicia - Sara Esteban; Yolanda Valcárcel; Myriam Catalá; Miguel González Castromil (Elsevier, 2012)
Objective: To monitor the presence of pharmaceutical residues of 14 psychoactive drugs belonging to three therapeutic groups in the watersheds of Galicia (Spain). Method: Five sewage treatment plants were selected in the main cities of Galicia. Thirteen psychoactive pharmaceutical compounds and one metabolite were chosen. In addition, tap water samples were taken from public places and private residences in the selected cities. Results: In all the water samples analyzed, the highest concentrations corresponded to the group of anxiolytics. In particular, high concentrations of lorazepam were found in river and tap water samples. Conclusions: This investigation demonstrates the presence of psychoactive pharmaceuticals in the watersheds of the autonomous region of Galicia and the conversion of metabolites to parent compounds. This work also shows the need to increase environmental monitoring of watersheds and to improve sewage and drinking water treatment processes to remove these pharmaceuticals. Objetivo: Monitorizar la presencia de 14 fármacos psicoactivos pertenecientes a tres grupos terapéuticos en la cuenca de Galicia. Método: Se seleccionaron cinco estaciones depuradoras de aguas residuales en las principales ciudades de Galicia. Se escogieron trece compuestos farmacéuticos psicoactivos y un metabolito. Asimismo, se tomaron muestras de aguas del grifo de espacios públicos y privados en las ciudades seleccionadas. Resultados: En todas las muestras de agua analizadas, las mayores concentraciones han correspondido al grupo de los ansiolíticos, y especialmente el lorazepam ha aparecido en altas concentraciones en las muestras de aguas de río y del grifo. Conclusiones: Esta investigación demuestra la presencia de fármacos psicoactivos en las cuencas de Galicia y la reversión de los metabolitos a sus compuestos parentales. Asimismo, muestra la necesidad de incrementar la monitorización ambiental de las cuencas y de mejorar los procesos de tratamiento de las aguas residuales y potables para eliminar estos fármacos.